2021
DOI: 10.1111/petr.14129
|View full text |Cite
|
Sign up to set email alerts
|

Eligible neonatal donors after circulatory determination of death (Maastricht type III): A national survey of level III NICUs

Abstract: Background: Organ donation continues to increase worldwide, but in general paediatric patients remain less likely to receive a transplant. The inclusion of neonates as donors after cDCD should be considered in an effort to increase donation rates. Methods:The survey for a cross-sectional national study of potential cDCD neonatal donors (Maastricht type III) was sent to all 90 level III Spanish neonatal units to explore: 1) protocols, education, and specific opinions on donation and 2) potential cDCD that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…A recently published study of 90 Spanish NICUs over a 1‐year period found that 31 newborns could have been potential neonatal donors if they had been timely identified and referred. By contrast, only two potential donors were referred, resulting in a total of zero neonatal organ or tissue donations 5 . Therefore, we consider that, despite the low number of potential neonatal donors referred to the OPO from our NICU, each potential neonatal donor who may become an effective organ or tissue donor, could have a significant clinical impact on infants’ waiting list mortality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recently published study of 90 Spanish NICUs over a 1‐year period found that 31 newborns could have been potential neonatal donors if they had been timely identified and referred. By contrast, only two potential donors were referred, resulting in a total of zero neonatal organ or tissue donations 5 . Therefore, we consider that, despite the low number of potential neonatal donors referred to the OPO from our NICU, each potential neonatal donor who may become an effective organ or tissue donor, could have a significant clinical impact on infants’ waiting list mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies on neonatal donation consider eligible for neonatal organ donation those newborns with a minimum gestational age of 34 weeks and a minimum birth weight of 2 kg 3,5,6,27,28 . However, there are no universally accepted criteria for neonatal organ and tissue donation and each local OPO has its own criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations